The Teams Games Tournament (TGT) Learning Model to Improve Basic Sprint Running Techniques of Class IV of SD Negeri 5 Purwanegara - Ardiansah, Didi; Wijaya, Febri (Journal of Physical Education Innovation, 2025)
This study aims to examine the application of the Teams Games Tournament (TGT) learning model to improve the basic sprinting technique of fourth-grade students at SD Negeri 5 Purwanegara. The research employed a Classroom Action Research (CAR) design consisting of two cycles, each involving the stages of planning, action, observation, and reflection. The study used a one-group pretest-posttest design involving a sample of 24 students, comprising 10 male and 14 female participants. The students' sprinting technique skills were assessed using a rubric-based evaluation of basic sprinting techniques. Data analysis was conducted using a repeated measures ANOVA test with SPSS version 27. The results showed that the Greenhouse-Geisser corrected value in the Tests of Within-Subjects Effects table indicated a significant p-value of 0.001 (p < 0.05). This means there was a statistically significant difference in the average improvement of students’ basic sprinting technique after applying the TGT learning model. Based on the results, it can be concluded that the application of the Teams Games Tournament (TGT) model in physical education activities effectively improves students’ basic sprinting techniques.